2015
DOI: 10.1111/1467-9817.12062
|View full text |Cite
|
Sign up to set email alerts
|

How speechreading contributes to reading in a transparent ortography: the case of Spanish deaf people

Abstract: The aim of the study is to describe the performance of deaf and hearing people while speechreading Spanish, a language with transparent orthography, and to relate this skill to reading efficiency. Three groups of 27 participants each were recruited: a group of deaf participants, a chronological age‐matched hearing group and a reading age‐matched hearing group. All three were tested on vocabulary, phonological awareness, reading speed, speechreading and, only in the group of deaf people, speech intelligibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The proportion of variance in single-word reading scores explained by the models in the current study was notably high for both deaf (R 2 = .75) and hearing children (R 2 = .94), which may in part reflect our use of latent variable models, which control for measurement error (see Hjetland et al, 2019). Study 1 replicated the positive relationship between speechreading and single-word reading in deaf children (e.g., Harris et al, 2017a;Kyle et al, 2016;Rodríguez-Ortiz et al, 2017). Importantly, our data also showed that, in deaf children, the relationship between speechreading and single-word reading was fully mediated by phonological awareness.…”
Section: Discussionsupporting
confidence: 59%
“…The proportion of variance in single-word reading scores explained by the models in the current study was notably high for both deaf (R 2 = .75) and hearing children (R 2 = .94), which may in part reflect our use of latent variable models, which control for measurement error (see Hjetland et al, 2019). Study 1 replicated the positive relationship between speechreading and single-word reading in deaf children (e.g., Harris et al, 2017a;Kyle et al, 2016;Rodríguez-Ortiz et al, 2017). Importantly, our data also showed that, in deaf children, the relationship between speechreading and single-word reading was fully mediated by phonological awareness.…”
Section: Discussionsupporting
confidence: 59%
“…It was expected that speechreading would predict reading in the OD group, given other research findings of its role in deaf reading (Kyle et al., ; Kyle & Harris, ; Rodríguez‐Ortiz, Saldaña, & Moreno‐Perez, ). Speechreading was a consistent correlate of decoding literacy for our OD participants, but not once vocabulary and/or phonological skills were controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…In order to measure reading ability at the sentence level we used the collective test of reading efficiency ("Test Colectivo de Eficacia Lectora" TECLE; Carrillo & Marin, 1997) which has been used in previous studies of deaf readers in Spanish (Domínguez et at., 2014;Rodríguez Ortiz et al, 2015). This test provides a combined measure of reading speed and comprehension.…”
Section: Sentence Reading Testmentioning
confidence: 99%